Educational Quality Transformation at MAN 2 Banyumas Through a Total Quality Management (TQM) Approach - Muhamad Siswanto (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
Education in Indonesia plays a crucial role in developing high-quality human resources, yet it continues to face major challenges related to quality, equity, and relevance to global needs. One affected sector is the madrasah, which is often perceived as lagging behind general schools, particularly in terms of quality management and resources. Total Quality Management (TQM) is an approach that can enhance the quality of education in madrasahs through continuous improvement in management, teaching, and evaluation. This study employs a qualitative method. The findings reveal that the implementation of TQM at MAN 2 Banyumas has led to significant transformations in both management and educational practices. Guided by the principle of continuous improvement, all elements of the madrasah are actively engaged in quality enhancement through planning, monitoring, and evaluation processes involving all stakeholders. A more participatory and collaborative leadership style has fostered open communication between the school and parents, strengthening an organizational culture that encourages active contributions from every individual. TQM has also improved the quality of teaching and curriculum—not only academically but also in the development of students’ life skills and character—through ongoing evaluation. Parental involvement in the learning process has been reinforced, fostering stronger ties between the madrasah and families. Furthermore, TQM in student services and management enables earlier problem identification and more effective solutions, resulting in a more holistic and meaningful learning experience.